(untitled) (REMUNOM, 2024)
Burnout Syndrome is a psychosocial phenomenon that significantly affects the mental and physical health of nursing professionals. This article aims to analyze the impact of Burnout Syndrome on nurses’ quality of life and performance. The research was conducted through a review of scientific literature, addressing the concepts, causes, and consequences of this syndrome. Studies showing the prevalence of Burnout among nurses, especially in highly demanding work environments such as intensive care units and emergency rooms, were included. Additionally, prevention and treatment strategies for Burnout are discussed, emphasizing the importance of both individual and organizational interventions to mitigate the effects of this condition. The article concludes that Burnout not only compromises the health of nurses but also the quality of patient care, highlighting the need for the implementation of support and wellness policies in the workplace.